Parallel compensator for zero dynamics stabilization in fluidized bed spray granulation. (August 2022) - Palis, Stefan
Abstract: This contribution is concerned with the stabilization of continuous fluidized bed spray granulation processes with external sieve mill cycle. To keep the overall mass of particles inside the granulation chamber in well-defined bounds these processes are in general operated with a mass controller. This configuration is well-known to become unstable for certain ranges of the milling diameter. Here, the instability results in a nonlinear limit cycle of the particle size distribution. As has been shown in a previous contribution the stability problem is not inherent to the process, which is open-loop stable over a wide range of operating conditions. In fact, the root cause for the instability is the mass controller, which interacts with the unstable zero dynamics of the granulation process. To overcome this problem a parallel compensator will be designed, which allows to stabilize the process zero dynamics and thus solves the problem of control induced instabilities. Highlights: Stabilization of continuous fluidized bed spray granulation with sieve mill cycle. Zero dynamics stabilization of continuous granulation under mass control operation. Robustness analysis of the proposed parallel compensator based control scheme.